Plasmonic Seasoning: Giving Color to Desktop Laser 3D Printed Polymers by Highly Dispersed Nanoparticles. Issue 15 (25th May 2020) - Hupfeld, Tim; Wegner, Andreas; Blanke, Meik; Doñate‐Buendía, Carlos; Sharov, Vladyslav; Nieskens, Simon; Piechotta, Markus; Giese, Michael; Barcikowski, Stephan; Gökce, Bilal
Abstract: Material development is key for continuing the exponential growth in the field of 3D printing. However, 3D printing of polymers by laser powder bed fusion (PBF‐LB) still is limited to a few polymer powder materials, which restricts the range of applications. Tailoring the chemical, rheological, mechanical, or optical properties of the feedstock powder to the requirements of the laser printing process poses a significant challenge. In order to meet global trends in the commercialization of desktop 3D printers, the use of inexpensive and compact diode lasers for PBF‐LB in the visible or near‐infrared range is highly desired. However, at present, only black objects can be printed by desktop laser printers since only commercial carbon black‐based composite powders meet their laser absorption requirements. In this study, a route for tuning the absorption properties of thermoplastic polyurethane polymers and incorporating color into printed objects by using minute amounts (i.e., 0.01 vol%) of highly dispersed plasmonic silver nanoparticles is reported, presenting a new way for colored parts to be produced through laser 3D printing. Abstract : In order to meet global trends in additive manufacturing, development of advanced feedstock materials, tailored for the additive process, is crucial. In this study, minute amounts of plasmonic nanoparticles are adsorbed on polymer powder by colloidal additivation to enable near‐field‐enhanced 3D printing of the polymer by laser powder bed fusion.